2001
DOI: 10.1038/sj.cgt.7700371
|View full text |Cite
|
Sign up to set email alerts
|

Hammerhead ribozyme against γ-glutamylcysteine synthetase sensitizes human colonic cancer cells to cisplatin by down-regulating both the glutathione synthesis and the expression of multidrug resistance proteins

Abstract: Multidrug resistance in cancer cells is often associated with an elevation in the concentration of glutathione ( GSH ) and the expression of -glutamylcysteine synthetase ( -GCS ), a rate -limiting enzyme for GSH. We constructed a hammerhead ribozyme against a -GCS heavy subunit ( -GCSh ) mRNA transcript and transfected it to human colonic cancer cells ( HCT8DDP ) resistant to cisplatin ( CDDP ). The effect of the ribozyme transfection on the drug resistance of cancer cells was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Our results are in agreement with data demonstrating that most c-Myc phenotypes can be explained by the activation/repression of the target genes set under its control (Iida et al, 2001;Zeller et al, 2003). In the context of drug response, Park et al (2002) demonstrated that overexpression of c-Myc can promote survival through activation of the ornithine decarbox- The role of ␥-GCS on the c-Myc-dependent drug response is not limited to CDDP.…”
Section: Downloaded Fromsupporting
confidence: 93%
“…Our results are in agreement with data demonstrating that most c-Myc phenotypes can be explained by the activation/repression of the target genes set under its control (Iida et al, 2001;Zeller et al, 2003). In the context of drug response, Park et al (2002) demonstrated that overexpression of c-Myc can promote survival through activation of the ornithine decarbox- The role of ␥-GCS on the c-Myc-dependent drug response is not limited to CDDP.…”
Section: Downloaded Fromsupporting
confidence: 93%
“…Northern Blot Analysis-A 764-bp DNA fragment (bp 865-1628) of fulllength ␥-GCS heavy subunit cDNA was obtained by digestion with PstI (29). The probes were radiolabeled with 32 P using a random primer labeling kit (Takara Biomedicals, Shiga, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Based on prior reports indicating that some of the ABC transporters may be implicated in the Pt drug accumulation defect found in resistant cells [22,23], we compared the level of expression of MRP1 -MRP4 and BCRP in the IGROV-1 and IGROV-1/OHP cells ( Figure 2). The MRP2, MRP3 and BCRP were not expressed in either cell type.…”
Section: Western Blot Analysis Of Levels Of Abc Transportersmentioning
confidence: 99%
“…Cells that have acquired resistance to cisplatin often have impaired drug uptake [15] and this has been linked to altered expression of genes involving copper metabolism [16][17][18][19][20][21]. Additional studies have implicated members of the ATP binding cassette (ABC) family of transporters such as Multidrug resistance associated protein (MRP) 2 and MRP1 in the accumulation defects found in cisplatin-resistant cells [22,23]. Based on similarity to other members of this family [24], it is likely that other ABC transporters are involved in regulating sensitivity to the Pt compounds.…”
Section: Introductionmentioning
confidence: 99%